An Experimental Study of Sub-1 GHz Frequency-Hopping-Based 6LoWPAN Mesh Networking for Smart-Grid Applications - Kim, Wonsoo; Vijayasankar, Kumaran; Chouteau, Mickael; Zhou, Jianwei (Journal of Computer Networks and Communications, 2019)
This paper presents an experimental study of a multihop Internet Protocol Version 6 over Low-Power Wireless Personal Area Networks (6LoWPAN)-based mesh system that uses un-slotted channel hopping (USCH) medium access control (MAC). Designers of wireless smart-grid networks are using (or looking to use) the Sub-1 GHz spectrum, given its longer radio range compared to the traditional 2.4 GHz spectrum used in Wi-Fi® or Bluetooth® low energy. The frequency-hopping (FH) technique is attractive in this area, as it provides improved robustness and longer range owing to the higher transmission power that regulatory requirements allow. Although Sub-1 GHz allows for a longer range, smart-grid networks deployed over a large geographic area still require multiple hops to provide the required coverage. Many proprietary and standards-based solutions have been proposed to implement such a networking protocol. Notable specifications in this area include the Field Area Networks (FAN) specification from the Wi-SUN (smart utility networks) Alliance and the JupiterMesh specification from the Zigbee Alliance. Little is known about the performance of FH systems over a multihop network, however. This paper presents an implementation of an FH-based multihop networking protocol based on the Texas Instruments (TI) SimpleLink™ TI 15.4-stack, with an experimental study of such a system over multiple hops compared to a non-frequency-hopping (non-FH) system. Results show that the proposed FH-based 6LoWPAN mesh system significantly improves network coverage, network capacity, and communication robustness to interference while demonstrating coexistence capabilities.